Peran Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Pegawai Dengan Motivasi Ekstrinsik sebagai Variabel Moderating pada KPP Pratama Semarang Candisari - Sudarmaji, Arip; Wardoyo, Paulus; Budiati, Yuli (Universitas 17 Agustus 1945 Samarinda, 2025)
This Study aims to analyze the role of transformational leadership and organizational culture on employee performance with extrinsic motivation as a moderating variable in KPP Pratama Semarang Candisari. This study used quantitative methods by using questionnaires to collect the necessary data. The sample in this study amounted to 104, obtained through the census method. Structural equation model (SEM) was used to analyze data with Partial Least Squares (PLS) tool version SmartPLS 3.2.9. The finding showed that transformational leadership and organization culture has a significant positive directly effect on employee performance. Extrinsic motivation has a positive and significant effect in moderating the influence of transformational leadership on employee performance. Extrinsic motivation has a positive and significant effect in moderating the influence of organizational culture on employee performance.